2014
DOI: 10.1175/jcli-d-14-00163.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Atmosphere and Land Surface Initial Conditions on Seasonal Forecasts of Global Surface Temperature

Abstract: The impact of land surface and atmosphere initialization on the forecast skill of a seasonal prediction system is investigated, and an effort to disentangle the role played by the individual components to the global predictability is done, via a hierarchy of seasonal forecast experiments performed under different initialization strategies. A realistic atmospheric initial state allows an improved equilibrium between the ocean and overlying atmosphere, increasing the model predictive skill in the ocean. In fact,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 58 publications
3
18
0
Order By: Relevance
“…Land‐atmosphere coupling , which is the mutual interaction between land surface and atmosphere, plays an important role in the predictability of the climate system by transferring and modulating soil state anomalies to the atmosphere. As demonstrated more than 30 years ago by the experiments of Shukla and Mintz [] and strongly restated in the 2001 American Meteorological Society Council [ American Meteorological Society Statement , ], knowledge of land surface initial condition is imperative for subseasonal [ Guo et al ., ] and seasonal [ Materia et al ., ] predictions.…”
Section: Land Surfacementioning
confidence: 99%
“…Land‐atmosphere coupling , which is the mutual interaction between land surface and atmosphere, plays an important role in the predictability of the climate system by transferring and modulating soil state anomalies to the atmosphere. As demonstrated more than 30 years ago by the experiments of Shukla and Mintz [] and strongly restated in the 2001 American Meteorological Society Council [ American Meteorological Society Statement , ], knowledge of land surface initial condition is imperative for subseasonal [ Guo et al ., ] and seasonal [ Materia et al ., ] predictions.…”
Section: Land Surfacementioning
confidence: 99%
“…Numerous studies have indicated that the persistence of soil moisture anomalies is from weeks to several months, both in observations (Entin et al, ; Ghannam et al, ; Hollinger & Isard, ; Liu et al, ; Orth & Seneviratne, ; Orth, ; Seneviratne & Koster, ; Vinnikov et al, ; Vinnikov & Yeserkepova, ) and in model simulations (Dirmeyer, ; Douville, ; Fennessy & Shukla, ; Ferranti & Viterbo, ; Guo et al, ; Hirsch et al, ; Kanae et al, ; Koster et al, ; Koster et al, ; Koster & Suarez, ; Materia et al, ; Paolino et al, ; Qi & Song, ; Schlosser & Milly, ; Seneviratne et al, ; Seneviratne & Koster, ; Wu & Dickinson, ; Xiang et al, ). Moreover, Langford et al () examined the decadal variability in precipitation over southwestern North America, and found the most of the variability appears to be explained by local anomalies associated with land‐atmosphere feedbacks, in which soil moisture plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…(Cohen et al 2014, p. 631), or Suckling andSmith (2013) and Materia et al (2014). Although by increasing ensemble size an arbitrarily low-amplitude atmospheric response can be made to pass statistical significance tests, utility of small-amplitude response for anticipating evolution of the earth system, and its usefulness for making skillful prediction still remains marginal.…”
Section: Introductionmentioning
confidence: 99%